v-src induction of the TIS10/PGS2 prostaglandin synthase gene is mediated by an ATF/CRE transcription response element. - Xie, W (1994)
We recently reported the cloning of a mitogen-inducible prostaglandin synthase gene, TIS10/PGS2. In addition to growth factors and tumor promoters, the v-src oncogene induces TIS10/PGS2 expression in 3T3 cells. Deletion analysis, using luciferase reporters, identifies a region between -80 and -40 nucleotides 5' of the TIS10/PGS2 transcription start site that mediates pp60v-src induction in 3T3 cells. This region contains the sequence CGTCACGTG, which includes overlapping ATF/CRE (CGTCA) and E-box (CACGTG) sequences. Gel shift-oligonucleotide competition experiments with nuclear extracts from cells stably transfected with a temperature-sensitive v-src gene demonstrate that the CGTCACGTG sequence can bind proteins at both the ATF/CRE and E-box sequences. Dominant-negative CREB and Myc proteins that bind DNA, but do not transactivate, block v-src induction of a luciferase reporter driven by the first 80 nucleotides of the TIS10/PGS2 promoter. Mutational analysis distinguishes which TIS10/PGS2 cis-acting element mediates pp60v-src induction. E-box mutation has no effect on the fold induction in response to pp60v-src. In contrast, ATF/CRE mutation attenuates the pp60v-src response. Antibody supershift and methylation interference experiments demonstrate that CREB and at least one other ATF transcription factor in these extracts bind to the TIS10/PGS2 ATF/CRE element. Expression of a dominant-negative ras gene also blocks TIS10/PGS2 induction by v-src. Our data suggest that Ras mediates pp60v-src activation of an ATF transcription factor, leading to induced TIS10/PGS2 expression via the ATF/CRE element of the TIS10/PGS2 promoter. This is the first description of v-src activation of gene expression via an ATF/CRE element.